FAKTOR-FAKTOR YANG MEMPENGARUI PERSEPSI MASYARAKAT TERHADAP BUDIDAYA TANAMAN KAKAO (Theobroma cacao L.) (Studi Kasus di Kecamatan Dagangan Kabupaten Madiun) - Mustika Wardhani, Ratna; Prasetiyo, Edy (JURNAL AGRI-TEK, 2016)
Cocoa is the economic mainstay of the plantation crop farmers in the area of Madiun Country, but the production and productivity of cocoa is still relatively low. Farming is still traditionally run like without the application of fertilizers, pest control (OPT) is not optimal and maximum maintenance such as pruning yet implemented. Therefore cocoa unable to give a maximum contribution to the income of the people in the district of Madiun. This study aims to determine the factors that affect the public perception for the cultivation of cocoa. The research was conducted in the village of the District Merchandise roll of Madiun. While research method implemented is descriptive research method and analysis method used is the method of Multiple Linear Regression analyst. The results of the study can be summarized as follows that the negative factors that influence public perception for the cultivation of cocoa is education (x1), the number of dependents (x2), age of the cocoa plant (x3), while the positive effect on public perception of aquaculture cocoa crop is the total land area (x4).Keywords: Perception, Society, Cocoa Plant